Relationship between the temporomandibular joint and vocal function: A literature review - Fuentes Aracena, Christopher (Revista de Investigación en Logopedia, 2022)
The study of the temporomandibular joint and its relationship with vocal function has received little attention from researchers. The main repercussions of this directly affects the work and decision making of clinicians. The objective of this article is to analyse the evidence that relates the temporomandibular joint to both normal and pathological vocal function. A literature review was carried out by analysing papers found in the PubMed, EBSCOHost, Scielo and Scopus databases. The evaluation of each study was done according to their title, abstract and eligibility criteria. The analysed papers showed an association between the temporomandibular joint and vocal function. Severe temporomandibular dysfunction negatively affects voice perception, while mandibular descent allows greater vocal intensity, optimises resonance and facilitates the control of the fundamental frequency.